Nanotechnology Applications to HIV Vaccines and Microbicides - Boyapalle, Sandhya (Medknow Publications & Media Pvt Ltd, 2012)
Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) remains one of the most serious threats to global health. Today there are no HIV vaccines which can prevent HIV infection. All of the candidates being studied are in the experimental stage. Preventive vaccine candidates are being tested in HIV-negative people to see if they can prevent infection. With of the development of a safe and effective vaccine still likely to be years away, topical microbicide formulations that are applied vaginally and rectally are receiving greater interest as an effective alternative to slow down the global spread of HIV. Current microbicide trials that aim to prevent the sexual transmission of HIV are using gels, creams, rings, films and there is also work underway to explore other types of ‘delivery’ systems. There have been numerous reports on safety and lack of toxicity of the application of nanotechnology for targeted delivery and slow, sustained release of drugs, proteins, peptides or nucleic acids by any route to maximize effectiveness and minimize adverse effects. The application of nanotechnology for targeting drugs and macromolecules to specific tissues or cells is one of the most important areas in nanomedicine research. Thus far nanoparticles provide a strong platform to combine protein and DNA based vaccines/microbicides and will facilitate the production, preclinical evaluation and clinical testing in the future.